2009
DOI: 10.1017/s0022029909990434
|View full text |Cite
|
Sign up to set email alerts
|

Casein retention in curd and loss of casein into whey at chymosin-induced coagulation of milk

Abstract: Impact of milk protein composition on casein (CN) retention in curd during the milk coagulation process was studied using a model cheese making system. Individual milk samples from 110 cows in mid lactation of the Swedish Red and Swedish Holstein breeds with known genotypes of beta-casein, kappa-casein and beta-lactoglobulin were defatted, coagulated with chymosin, subjected to syneresis and subsequent pressing simulated by centrifugation. The results indicated that kappa-casein concentration of milk plays an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 26 publications
1
39
2
5
Order By: Relevance
“…This explains the common practice in commercial cheese making of adding calcium chloride in cheese making before the enzymatic coagulation step so coagulation takes place normally, but aging cheeses with high citrate levels develop better flavors (Dudley and Steele, 2005;Brickley et al, 2009). Furthermore, an increasing concentration of lactose in milk has been shown to exert a beneficial effect on the formation of acid-induced milk gels (Hallén et al, 2010). In this context, lactose is the most important osmoregulator of milk synthesis and is, to some extent, correlated with the total protein and casein content of milk, whereby lower levels of citrate content in milk induced the caseins to become overloaded with calcium, and then precipitate (Hallén et al, 2007).…”
Section: Association Between Target Gene Genotypes and Citrate Contentmentioning
confidence: 92%
“…This explains the common practice in commercial cheese making of adding calcium chloride in cheese making before the enzymatic coagulation step so coagulation takes place normally, but aging cheeses with high citrate levels develop better flavors (Dudley and Steele, 2005;Brickley et al, 2009). Furthermore, an increasing concentration of lactose in milk has been shown to exert a beneficial effect on the formation of acid-induced milk gels (Hallén et al, 2010). In this context, lactose is the most important osmoregulator of milk synthesis and is, to some extent, correlated with the total protein and casein content of milk, whereby lower levels of citrate content in milk induced the caseins to become overloaded with calcium, and then precipitate (Hallén et al, 2007).…”
Section: Association Between Target Gene Genotypes and Citrate Contentmentioning
confidence: 92%
“…The yield and composition of major bovine milk proteins determine the value of the product, depending on how the milk will be used. For cheese making a higher casein content, particularly higher κ-CN, correlates to increased curd yield, stronger curd firmness, and less casein loss in whey (Hallen et al, 2010). The composition of milk and milk proteins is influenced by many factors.…”
mentioning
confidence: 99%
“…Wedholm et al (2006) reported that cheese yield was improved at increasing concentrations of κ-casein (κ-CN), α S 1-casein (α S 1-CN), β-casein (β-CN) and β-lactoglobulin (β-LG) in milk. Hallén et al (2010) also detected that increased κ-CN was associated with higher amount of casein retained in curd.…”
Section: Introductionmentioning
confidence: 85%